THE DIGITAL ACCOUNTING ENTREPRENEURSHIP COMPETENCY FOR SUSTAINABLE PERFORMANCE OF THE RURAL MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES): AN EMPIRICAL REVIEW - Hasbolah, Farhana; Rosli, Mohamad Hafiz; Hamzah, Hanissah; Omar, Siti Aisyah; Bhuiyan, Abul Bashar (International Journal of Small and Medium Enterprises, 2021)
A year has passed since the Covid-19 pandemic hit the world and no one could have imagined that it would leave such a massive impact on the world economic landscape. The most affected groups are the Rural Micro, Small, and Medium Enterprises (MSMEs) and micro-entrepreneurs. With the implementation of the Movement Control Order (MCO), the business owners are in dilemma in the way to sustain and maintain their businesses. They need to scrutinize the ability of their businesses to continue operations amid the Covid-19 pandemic. Besides, these business owners were forced to explore new strategies to interact with customers and to simplify transaction processes. A new shift or new normal of the spending habits are formed where individuals are more interested to perform online shopping, and this creates an ideal market environment for business owners to accelerate, test, and launch new experience-driven mobile applications and websites across all their digital platforms. Hence, this study is an empirical attempt to formulate the digital accounting competency model for rural MSMEs. The available online empirical recourses by the name of digital accounting entrepreneurship and sustainable performance of the rural MSMEs in different online database sources such as Google Scholars, Springer Link, Wiley, Science Direct, JSTOR, Emerald full text, Scopus, and EBSCO HOST were used for the review. The review findings hitherto show that digital accounting entrepreneurship has a significant role in ensuring the sustainable performance of the rural MSMEs, especially for entrepreneurial competency, marketing capability, knowledge sharing, financial resources, technology usage, drive change and engagement, and individual competency is considered the most influencing factors toward sustainable performance among the rural MSMEs in the world. This finding, therefore, warrants a more in-depth analysis to develop a digital accounting entrepreneurship competency model.